Age is positively associated with HDL-cholesterol among African Americans in cross-sectional analysis: the Jackson Heart Study - Harman, Jane L. (2011)
BACKGROUND: African Americans have historically had high HDL-C compared to other races and ethnicities. OBJECTIVE: We sought to characterize whether there is a cross-sectional association between age and HDL-C in a contemporary community-based study of African Americans. METHODS: Cross-sectional data was modeled by logistic regression for predictors of HDL-C among African-Americans, ages 35–74, participating in the baseline examination of a community-based study of cardiovascular disease in Jackson, MS, during 2000–2004. After excluding persons taking lipid-lowering medications, hormone replacement therapy, oral contraceptives, or thyroid replacement, the analytical data set comprised 2420 persons (1370 women, 1050 men). RESULTS: HDL-C had a significant positive association with age after controlling for serum triglycerides, sex, waist circumference, percent dietary calories from carbohydrates, alcohol use, and leisure physical activity. Sex was a significant effect modifier of this relationship, whereby the increase in HDL-C with age was steeper for women than for men. CONCLUSIONS: Cross-sectional analysis found a positive association of HDL-C with age while controlling for triglycerides. Careful evaluation of longitudinal data will be needed to confirm whether this is a true effect of aging, or a cohort or survivor effect.